Opportunity, mobility and inequality - Bandyopadhyay, Sanghamitra; Rodríguez, Juan Gabriel (Research on economic inequality ;, 2025)
Research on Economic Inequality is a well-established publication of quality research. Volume 31 provides original research on intergenerational earnings mobility, the factors determining adult health inequality, the evolution of wealth inequality in different regions of the world, inequality of employment opportunities, and the effects of the type of labour agreement on wage inequality and on an extended measure (income plus wealth) of well-being. Opportunity, Mobility and Inequality presents newly published, rich datasets and deepens our understanding of these issues, uncovering novel innovations around how we conceive and measure such economic entities.